In Mice the Efficiency of Immunization With Venezuelan Equine Encephalomyelitis Virus TC-83 is Transiently Increased by Dehydroepiandrosterone - Negrette, Beatriz; Bonilla, Ernesto; Valero, Nereida; Giraldoth, Débora; Medina Leendertz, Shirley; Añez, Florencio (Investigación Clínica, 2009)
To determine whether treatment with dehydroepiandrosterone (DHEA) improves the efficiency of immunization against the Venezuelan Equine Encephalomyelitis (VEE) virus, mice were vaccinated with the TC-83 VEE virus. DHEA (10 mg/kg) was administered in a single dose, 4 hours before vaccination. IgM antibody titers were determined at days 7, 14 and 21 post-immunization. Treatment with DHEA increased antibody titers at day 14 after immunization. Mice were challenged with live VEE virus at day 21, and viral titers were plaque assayed in chicken embryo fibroblasts from days 2 to 5 post-infection. After the challenge, viremia decreased on day 2 and brain virus levels were reduced at day 4 in mice treated with DHEA. These results suggest that DHEA treatment could enhance the efficiency of immunization against VEE virus in mice.